Chemical Reaction Effects on Maxwell Base MHD Fluid Flow of Nonomaterial over Vertical Moving Surface with Radiation - et. al., KonduruVenkateswaraRaju, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research report investigated the laminar Maxwell Nanofluid boundary flow of MHD over a vertically moving flat porous plate in 2D (two dimensional). Consideration is given to viscous dissipation in conjunction with heat absorption. By employing appropriate similarity transformations, the governing PDEs are converted to a system of coupled nonlinear ODEs. Bvp4c solves the condensed equations using the firing technique. Graphs and tables illustrate the impacts of various parameters on velocity, temperature, and concentration profiles. We also evaluated the effect of multiple parameters on the skin friction coefficient, heat and mass transfer rate, and the Nusselt and Sherwood numbers, respectively.